The Influence of Servant Leadership, Self Awareness, and Workload on Organizational Citizenship Behavior (OCB) and Employee Performance at BAPPEDA East Java Province - Patria, Rio; Riyadi, Slamet; Sumiati (MultiTech Publisher, 2024)
This study aims to examine the influence of Servant Leadership, Self Awareness, Workload on Organizational Citizenship Behavior (OCB), and Employee Performance at Badan Perencanaan Pembanguna Daerah (BAPPEDA) Provinsi Jawa Timur. The research was conducted using a quantitative approach and data were collected from employees working at BAPPEDA Provinsi Jawa Timur. The collected data is analyzed using the Structural Equation Modeling (SEM) PLS method with the Smart PLS Version 4.0 software. The respondents for this study were 118 employees out of a total of 137 employees at BAPPEDA Provinsi Jawa Timur. The data collection instrument was measured using a Likert scale. The research findings indicate that Servant Leadership significantly influences OCB but does not significantly affect Employee Performance. On the other hand, Self Awareness significantly influences both OCB and Employee Performance, while Workload does not significantly affect OCB but has a significant impact on Employee Performance. Additionally, OCB significantly influences Employee Performance. These results highlight the importance of implementing Servant Leadership and fostering Self Awareness to encourage OCB, while Workload has a greater impact on employee performance. Interestingly, the implementation of servant leadership does not seem to drive employee performance at BAPPEDA Provinsi Jawa Timur, however the high level of OCB in BAPPEDA of East Java Province can enhance employee performance. Keywords: Servant Leadership, Self-Awareness, Workload, Organizational Citizenship Behavior, Employee Performance